Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1126/science.3086977
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Human p I 7 Interleukin-1 for Pancreatic Islets of Langerhans

Abstract: Activated mononuclear cells appear to be important effector cells in autoimmune beta cell destruction leading to insulin-dependent (type 1) diabetes mellitus. Conditioned medium from activated mononuclear cells (from human blood) is cytotoxic to isolated rat and human islets of Langerhans. This cytotoxic activity was eliminated from crude cytokine preparations by adsorption with immobilized, purified antibody to interleukin-1 (IL-1). The islet-inhibitory activity and the IL-1 activity (determined by its comito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
241
1
6

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(261 citation statements)
references
References 22 publications
9
241
1
6
Order By: Relevance
“…Values after 3 days exposure to IL-1β (50 U/ml) and IFN-γ (1,000 U/ml) were determined by ELISA and with Griess reagent protocol respectively, and are expressed as means±SEM from three to four independent experiments. One superscript symbol p≤0.05, two superscript symbols p≤0.01; three superscript symbols p≤0.001, four superscript symbols p≤0.0001: ( †) compared with control C57BL/6 islets (under similar conditions); (*) compared with control C57BL/6 islets (no cytokines added); ( ‡) compared with Irf-1 −/− islets (no cytokines added) only minor effects on cell viability [6,38]; they also show that blocking IL-1β action with IL-1Ra can prevent the deleterious effects [24,34,[39][40][41][42]. Although this was confirmed in our study, we observed abnormal glucosestimulated insulin release from Irf-1 −/− islets under basal conditions that could not be corrected by IL-1Ra, indicating an independent defect in beta cell secretory machinery of Irf-1 −/− islets.…”
Section: Discussionmentioning
confidence: 99%
“…Values after 3 days exposure to IL-1β (50 U/ml) and IFN-γ (1,000 U/ml) were determined by ELISA and with Griess reagent protocol respectively, and are expressed as means±SEM from three to four independent experiments. One superscript symbol p≤0.05, two superscript symbols p≤0.01; three superscript symbols p≤0.001, four superscript symbols p≤0.0001: ( †) compared with control C57BL/6 islets (under similar conditions); (*) compared with control C57BL/6 islets (no cytokines added); ( ‡) compared with Irf-1 −/− islets (no cytokines added) only minor effects on cell viability [6,38]; they also show that blocking IL-1β action with IL-1Ra can prevent the deleterious effects [24,34,[39][40][41][42]. Although this was confirmed in our study, we observed abnormal glucosestimulated insulin release from Irf-1 −/− islets under basal conditions that could not be corrected by IL-1Ra, indicating an independent defect in beta cell secretory machinery of Irf-1 −/− islets.…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid deposits are comprised primarily of islet amyloid polypeptide (IAPP), 5 a 37-amino acid peptide that is co-secreted with insulin by beta cells. Recent evidence suggests that IAPP aggregates trigger islet secretion of IL-1, which acts alone or in combination with other pro-inflammatory cytokines to impair beta cell insulin secretion (5,6). Human but not non-amyloidogenic rodent IAPP induces IL-1␤ synthesis in bone marrow-derived and intra-islet macrophages (7,8).…”
mentioning
confidence: 99%
“…cells and thyroid epithelial cells are susceptible to cytokine-mediated damage. In particular, the deleterious eflects of IL-1^ on pancreatic fi islet cells in vitro have been clearly established [61][62][63][64][65]. It has also been demonstrated that the exposure of fi islet cells to this cytokine leads to a potent inhibition of cell function.…”
Section: Cytokines and Effector Mechanisms In Autoimmune Diseasesmentioning
confidence: 87%
“…The eflect of IL-1 on fi islet cells in culture was found to be both time-and dose-dependent. Thus, acute exposure to IL-l/3 produced a stimulation of fi islet cell function with increased insulin production, whilst long-term exposure suppressed insulin production and release, ultimately leading to fi islet cell death [61,65]. The eflects described appear to be mediated by the binding of IL-1 to specific receptors [66] which has been demonstrated on both fi islet cells and thyrocytes [67,68], and seems to involve the generation of oxygen free radicals [69,70].…”
Section: Cytokines and Effector Mechanisms In Autoimmune Diseasesmentioning
confidence: 99%